Investigation of hospital-acquired infections prevalence and analysis of influencing factors: a case study of a specialized infectious disease hospital in Chongqing, 2017–2023 - Deng, Bing; Li, Peilin; Liu, Yalan; Xie, Juan; Huang, Yaling; Sun, Qingyun; Su, Shifang; Deng, Wenwen (Frontiers in Public Health, 2024)
Objective: This study aimed to investigate the prevalence of hospital-acquired infections (HAIs) and their main influencing factors in a specialized infectious disease hospital in Chongqing from 2017 to 2023, providing reference for the formulation of precise infection control measures. Methods: A retrospective cross-sectional survey method was employed, combining bedside investigations with medical record reviews.Surveys were conducted on all hospitalized patients on a certain day of the last week of October each year from 2017 to 2023. Data collected included patients' basic information, diagnosis, and hospital infection status. Statistical analysis, including retrospective case-control and multivariable logistic regression analysis, was performed to identify the risk factors for hospital infections. Results: The investigation compliance rate for the prevalence of HAIs in the specialized infectious disease hospital in Chongqing from 2017 to 2023 was greater than 96% each year.The prevalence rate of HAIs ranged from 0.89% to 2.52%. Hospital infection departments were mainly concentrated in general internal medicine, tuberculosis, and HIV/AIDS departments, accounting for 31.25%, 26.25%, and 23.75%, respectively.The most common infection site was the lower respiratory tract (54.22%), followed by bloodstream and urinary tract infections, each accounting for 9.64%. The predominant pathogens of hospital infections were Klebsiella pneumoniae and fungi.The utilization rate of antimicrobial drugs ranged from 20.75% to 33.25%, primarily for monotherapy. The rate of pathogen testing for therapeutic antimicrobial drug use was 82.84%, meeting national requirements. Multivariable logistic regression analysis revealed that the use of antibiotic (OR=7.46, 95%CI 2.54-21.89, P<0.001) and the presence of cardiovascular diseases (OR=26.69, 95%CI 6.69-106.54, P<0.001) increased the risk of HAIs.Conclusion: The prevalence of HAIs in specialized infectious disease hospitals remains stable, primarily concentrated in departments such as general internal medicine, tuberculosis, and HIV/AIDS. The lower respiratory tract is the main infection site, and comorbid cardiovascular diseases and antibiotic use are risk factors for HAIs. Therefore, to reduce the risk of hospital infections, it is necessary to strengthen the daily monitoring of key departments and the care of key patients. Further implementation of precise and effective infection control measures, including rational antibiotic use, regular infection monitoring and pathogen culture is warranted.